Rethinking Program Evaluation in Educational Technology - Kumar, David Devraj (Indian Journal of Educational Technology, 2021)
Ideas for rethinking program evaluation in educational technology in order to make informed decisions to reform teaching and learning are explored. The complexity of program evaluation when dealing with complex educational technology systems involving various subject disciplines, grade levels and the degree (e.g., how, where) to which it overlaps and/or integrates with each individual discipline and grade demands more comprehensive approaches to evaluation. A comprehensive evaluation model placed in real-world supportive and contextual factors with insights from classic evaluation methods is suitable for gaining a detailed layout of educational technology programs.